Assessment of a dose-response relationships between 1-week and 4-week cumulative training load and physical performance outcomes in elite youth soccer - Connolly, D. R.; Mercer, R.; McLean, B.; Rampinini, E.; Coutts, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: At present, little evidence is available relating to associations between training load and fitness in elite youth soccer players, or how these may vary across different age groups. This study aimed to evaluate the dose-response relationships between internal and external training load variables recorded over acute (1-week) and chronic (4-week) periods with changes in elite youth players physical fitness. METHODS: A retrospective observational design was employed to assess the relationship between training load and variations in measures of physical fitness across 5 competitive seasons (2017-18 to 2021-22). Three age groups (U16, U17 and U19) performed fitness tests aimed at assessing aerobic (Mognoni test), intermittent running (HIT test) and muscular qualities (Countermovement jump test (CMJ)), four times each season (preseason (PRE), start (IN1), middle (IN2) and end of season (IN3)). Internal and external training loads were quantified during every training session and match, and the sum of load accumulated over 1- and 4-weeks calculated for the subsequent analysis. Linear mixed models were applied to explore associations between six training load variables, across 1- and 4-week time frames, and changes in fitness test outcome measures. RESULTS: A significant effect for age group and test period was found for each of the three fitness tests (Mognoni, HIT and CMJ, p < 0.002). U19 and U17 recorded significantly higher scores Mognoni and HIT than U16 (p 0.280). Mognoni and HIT demonstrated a significant improvement from PRE to all in-season test periods and no significant difference across in-season periods. CMJ power was significantly different between the three age groups (p < 0.0002). CMJ did not significantly change between PRE and IN1 (p = 0.63) but there were increases between PRE and IN2 and IN3, respectively (p < 0.025). A small significant positive association was found between HIT and time spent >90% heart rate max (HR90%) recorded across 4-week period (p = 0.016, d = 0.21). Very high-speed running (VHSR) accumulated in 4-weeks had a small positive association with CMJ power (p < 0.0003, d = 0.23). CONCLUSION: The longitudinal approach, across a season and different age groups, provides an insight into the progression of youth soccer players physical capacity across different physiological assessments. Aerobic and HIT capacity improve throughout the preseason period, whilst muscular qualities (CMJ) increase in the later part of the season. Improvements in test outcomes were observed with load accumulated over the longer timeframe assessed, specifically a 4-week period in VHSR for CMJ and HR90% for HIT. More details regarding the periodization of load (i.e., frequency, duration, mode, intensity, and distribution of training) within the time frames assessed and how they are manipulated are important for informing applied practitioners and their decision-making process.